Ain't nobody's fool : the life and times of Dolly Parton - Ackmann, Martha (St. Martin's Press, an imprint of St. Martin's Publishing Group, 2025)
"A larger-than-life new biography of country music legend and philanthropist Dolly Parton. In Ain't Nobody's Fool: The Life and Times of Dolly Parton, Martha Ackmann chronicles the life of an American Original. From her impoverished childhood in the Smoky Mountains to international stardom as a singer, songwriter, actress, businesswoman, and philanthropist, Dolly Parton has exceeded everyone's expectations except her own. During a time when the Beatles set the standard for contemporary music, Dolly appeared on a local country music television show that her high school classmates thought was pure cornpone. The day after her high school graduation, she boarded a bus for Nashville, but record executives turned her down. One said her voice sounded like a screech owl. When Dolly finally got her foot in the door, her talent and focus catapulted her to the top of country charts, the pop world, and movie stardom. Yet her success came at a price. Shunned by many in Nashville who saw her ambition as a betrayal of her country music roots, Dolly became the target of death threats, lawsuits, and a judge who threatened to throw her in jail. She nearly collapsed on-stage and later succumbed to depression that pushed her to the brink, but she refused to be counted out and came back stronger than ever developing Dollywood, the amusement park that became the economic engine of East Tennessee, and founding the Imagination Library that provides free books to children around the world. Her philanthropy to health organizations led to creation of the Moderna COVID vaccine. And, finally, she returned to her roots, recording bluegrass albums that became the most celebrated of her unparalleled 60-year career. Ain't Nobody's Fool is a deep dive into the social, historical, and personal forces that made Dolly Parton one of the most beloved and unifying figures in public life and includes interviews with friends, family members, school mates, Nashville neighbors, members of her band, studio musicians, producers, and many others. It also features never before seen photographs and unearthed documents shedding light on her family's hardscrabble life. More than anything, Martha Ackmann's fresh and animated new book proves Dolly Parton knows just who she is and she ain't nobody's fool"-- Provided by publisher.